In search of Southeast Asia : (University of Hawaii Press, 1987)
This is a wonderful introduction to the history of Southeast Asia, ranging from the early modern period of the region to the influence of colonialism on the society and culture of Southeast Asian countries. Whether or not you've heard of similarly central and basic events or people in Southeast Asia is another question. Most people in English-speaking countries are a bit vague if asked about Arakan (a long independent kingdom now part of Burma or Myanmar) or Cebuano (one of the most important Philippine languages), Tu Duc (the last major emperor of Vietnam who died in 1883) or Kartini (a Javanese woman whose letters are a monument to modernization and change in Indonesia).